Pediatric brain stimulation : mapping and modulating the developing brain - Kirton, Adam; Gilbert, Donald L. (Pediatric neurologist) (Academic Press is an imprint of Elsevier, 2016)
Pediatric Brain Stimulation: Mapping and Modulating the Developing Brain presents the latest on this rapidly expanding field that has seen an exponential growth in publications over the past 10 years. Non-invasive modalities like TMS can painlessly map and measure complex neurophysiology in real patients. Neuromodulatory applications like rTMS and tDCS carry increasingly proven therapeutic applications. Rapidly advancing technological methodologies are increasing opportunities and indications. Despite all these benefits, applications in the more plastic developing brains of children are only just emerging. This book provides a comprehensive overview of brain stimulation in children. Chapters include Transcranial Magnetic Stimulation (TMS) fundamentals, brain stimulation in pediatric neurological conditions, and invasive brain stimulation. The main audience for this research will be those interested in applying brain stimulation technologies to advance clinical research and patient care, although a wide variety of clinicians and scientist will find this to be a valuable reference on brain stimulation with specific chapters on a variety of conditions. Provides an overview of recent findings and knowledge of pediatric brain stimulation and the developing brainEdited by renowned leaders in the field of pediatric brain stimulationPresents a great resource for basic and clinical scientists and practitioners in neuroscience, neurology, neurosurgery, and psychiatry